The impact of privatisation on socio-economic rights and services in Africa: the case of water privatisation in South Africa - De Vos, Pierre (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2004.